“Efecto del humus de lombriz sobre la producción del cultivo de col china híbrida (brassica capestris) Var. Pekinensis en Tarapoto-Perú” - Carranza Villalobos, Samuel (2006)
In the present work of study "Effect of the Humus of worm on the production of the cultivation of Hibrid Chinese Cabbage (Brassica campestris) var. Pekinensis in Tarapoto- Peru ". 1 look for the optimum/ good dose level of security that the production increases.The work was in the Found Miraflores of property of the faculty of Agronomy of the National University of San Martín, located in the sector from Ahuashiyacu to 3,5 kilometers of Tarapoto. The objectives of the work were to evaluate the effect of four levels of worm humus in sorne agronomic characteristics and on the yield of the cultivation of hybrid Chinese cabbage (Brassica campestris) Var. Pekinensis in Tarapoto- Peru, Was also to carry out the economic analisis of the treatments in study based on the relateonship benefiU cost to determine the profitability. The ground was of sandy frak type, with a strongly sour pH 4.85, half M.O of 3, 57% with a content of alf P20s (21, 7 kg/ha), in potassium with 140 kg/ha, etc. The design employee was of blocks totally at random, with four treatments and four repetitions. The following observations as/ like plant height to the crop, head diameter, yield kg/ha and the analysis benefiU cost, of wich the clases with worm humus had the best results to the witness in the varibles of growth , diameter and yield, but respect the benefit I cost went smalles to the withess, being the mast economic the T1 whose relation ship benefiUcost is of 8,35% with a net benefit of 25419,18 new suns and the less economic the treatment T4 with a relation ship of benefit I cost of 5,93% with a net benefit of 66060,94 new suns. But it is assumed that the residual effect leaves for more than two years wich is profitable to medium and on thew long term, according to the carried aut investigations.